Analisis Kesadaran Mahasiswa Yogyakarta Tentang Phishing Pada Online Banking - Lukman Wijaya; Erna Kumalasari Nurnawati (Universitas PGRI Yogyakarta, 2022)
Abstract Phishing is a form of semantic attack and is sometimes called with online identity theft, which aims to steal sensitive data such as usernames, passwords, and online banking details from its victims. In this study, we tried to measure the level of awareness of students in Yogyakarta about phishing crimes in online banking by using a quantitative descriptive method in which Google forms and interviews were used to collect data from students in Yogyakarta with 11 questions using both Google forms and interviews. With the results of this study, 77% of the total 40 Google Forms participants said they knew or really knew and 7 out of 10 interview participants said they understood. So it can be concluded that most students in Yogyakarta already know and understand what things can be done to avoid phishing in online banking. However, it is necessary to increase the level of student awareness of the security of their accounts. Keywords - Phishing, online banking, security, students